HEATING AND FREEZING EXPERIMENTS ON AQUEOUS FLUID INCLUSIONS IN ANHYDRITE: RECOGNITION AND EFFECTS OF STRETCHING AND THE LOW-TEMPERATURE FORMATION OF GYPSUM - Vanko D.A.; Bach W. (My University, 2005)
Aqueous fluid inclusions in anhydrite that are frozen during microthermometry commonly develop new daughter crystals. Heating these inclusions induces the new daughter crystals to decompose. Repeated cycles of crystal growth and decomposition may result in morphological changes of the fluid inclusions. This phenomenon of new mineral growth, presumed to represent the low-temperature hydrate, gypsum, has been recognized for over 20 years. Nevertheless, its occurrence and its significance to the determination of inclusion salinities are not widely appreciated. Similarly, the potential of inclusions in anhydrite to stretch when overheated is commonly assumed, yet tests demonstrating the phenomenon have not been reported. Changes in the ice melting temperature of aqueous inclusions in anhydrite before and after gypsum formation were documented, showing that hydration of the host anhydrite may significantly lower the ice melting temperature and increase the salinity of the residual inclusion fluid. Heating inclusions to induce gypsum to decompose results in the release of bound water, restoring the inclusions to their original salinity. The homogenization temperatures of inclusions that have undergone these phenomena are generally unchanged, indicating that the inclusions' specific volumes are unchanged. However, heating aqueous inclusions in anhydrite more than ten degrees or so above their homogenization temperature commonly results in stretching. Therefore, those who study aqueous inclusions in anhydrite must avoid the determination of ice melting temperatures if new gypsum daughter crystals are present, and must determine homogenization temperatures sequentially with rising temperature to avoid overheating and stretching.
Keywords: Fluid inclusions; Anhydrite; Gypsum; Microthermometry; Ocean Drilling Program